Arrhythmic Risk in Elderly Patients Candidates to Transcatheter Aortic Valve Replacement: Predictive Role of Repolarization Temporal Dispersion - Piccirillo, Gianfranco; Moscucci, Federica; Fabietti, Marcella; Parrotta, Ilaria; Mastropietri, Fabiola; Di Iorio, Claudia; Sabatino, Teresa; Crapanzano, Davide; Vespignani, Giulia; Mariani, Marco Valerio; Salvi, Nicolò; Magrì, Damiano (Frontiers in Physiology, 2019)
Background/Aim: Degenerative aortic valve stenosis (AS) is associated to ventricular arrhythmias and sudden cardiac death, as well as mental stress in specific patients. In such a context, substrate, autonomic imbalance as well as repolarization dispersion abnormalities play an undoubted role. Aim of the study was to evaluate the increase of premature ventricular contractions (PVC) and complex ventricular arrhythmias during mental stress in elderly patients candidate to the transcatheter aortic valve replacement (TAVR). Methods: In eighty-one elderly patients with AS we calculated several short-period RR- and QT-derived variables at rest, during controlled breathing and during mild mental stress, the latter being represented by a mini-mental state evaluation (MMSE). Results: All the myocardial repolarization dispersion markers worsened during mental stress (p<0.05). Furthermore, during MMSE, low frequency component of the RR variability increased significantly both as absolute power (LFRR) and normalized units (LFRRNU) (p<0.05) as well as the low-high frequency ratio (LFRR/HFRR) (p<0.05). Eventually, twenty-four (30%) and twelve (15%) patients increased significantly PVC and, respectively, complex ventricular arrhythmias during the MMSE administration. At multivariate logistic regression analysis, the standard deviation of QTend (QTesd), obtained at rest, was predictive of increased PVC (odd ratio: 1.54, 95% CI 1.14-2.08; p:0.005) and complex ventricular arrhythmias (odd ratio: 2.31, 95% CI 1.40-3.83; p:0.001) during MMSE. The QTesd showed the widest sensitive-specificity area under the curve for the increase of PVC (AUC: 0.699, 95% CI: 0.576-0.822, p<0.05) and complex ventricular arrhythmias (AUC: 0.801, 95% CI: 0.648-0.954, p<0.05). Conclusions: In elderly with AS ventricular arrhythmias worsened during a simple cognitive assessment, this events being a possible further burden on the outcome of TAVR. QTesd might be useful to identify those patients with the highest risk of ventricular arrhythmias. Whether the TAVR could led to a QTesd reduction and, hence, to a reduction of the arrhythmic burden in this setting of patients is worthy to be investigated.